ĐÁNH GIÁ ẢNH HƯỞNG CỦA PHÂN BÓN LÁ SINH HỌC Ca-OLIGOCHITOSAN-AMIN+TE ĐẾN SỰ SINH TRƯỞNG VÀ PHÁT TRIỂN CỦA CÂY RAU CẢI THÌA (Brassica chinensis L.) TRỒNG Ở CỦ CHI, THÀNH PHỐ HỒ CHÍ MINH - Nguyễn, Thị Nga; Lâm, Vân Hà; Đặng, Minh Nguyệt; Nguyễn, Hoàng Huynh; Trần, Vân Lâm; Ngô, Văn Tuấn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE EFFECTS OF BIOGRAPHIC FOLIAR Ca-OLIGOCHITOSAN-AMIN+TE ON GROWTH AND DEVELOPMENT OF BOK CHOY IN CU CHI, HO CHI MINH CITYEvaluation of the effects of Ca-Oligochitosan-Amin-TE biological foliar fertilizer on growth and development on bok choy (Brassica juncea L.) and mushy rot disease on bok choy, was carried out at the experimental farm of the Center for Applied Biotechnology High-tech Agriculture Application of Ho Chi Minh City, The experiment was carried out from May to November 2022, For bok choy, was conducted with 7 treatments, in which treatment 1 (control) sprayed with cold water, and treatment 2 (control) sprayed with specialized Ca-containing fertilizers for bok choy, from treatment 3 to treatment 7 spray Ca-Oligochitosan-Amin-TE biological foliar fertilizer with spray dosages: 1/400, 1/500, 1/600, 1/700 and 1/800, spray once every 7 days, The results showed that at the dose of 1/500 liter of water combined with organic fertilizer, the NPK decreased by 20% compared to farmers' practices, increasing the height, number of leaves/plant, fresh weight, and yield through the stages. Productivity and economic efficiency are calculated to increase by 18.5% and 47.1% respectively.